Bloom: Scaffolding Multiple Positive Emotion Regulation Techniques to Enhance Casual Conversations and Promote the Subjective Well-Being of Emerging Adults - Kyra Kozin; Sehar Mapara; Chajoong Kim; JungKyoon Yoon (Multimodal Technologies and Interaction)
This paper presents Bloom, a low-tech interactive artifact designed to enhance in-person social interactions among emerging adults. Drawing upon emotion regulation theories, the development of Bloom explores how multiple Positive Emotion Regulation (PER) techniques can be incorporated into an artifact that can effectively enhance users’ subjective well-being in their routines. By grounding on autobiographical research through design, we discuss the design methodology employed to develop a prototype that supports five PER techniques, along with key design features, and experiences of using Bloom. The chosen PER techniques are as follows: (1) being immersed and absorbed, (2) engaging in a collective, (3) creating a savoring atmosphere, (4) sharing the positive experience with others, and (5) infusing ordinary events with positive meaning. Through daily observations and reflections, we discuss key design features that have proven critical in engaging ourselves in PER, the benefits of utilizing diverse PER techniques to enhance our well-being, and implications for future behavioral intervention technologies.